1962
DOI: 10.1111/j.1749-6632.1962.tb34646.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood Groups in Chimpanzees, Horses, Sheep, Pigs, and Other Mammals

Abstract: The study of experimental immunohematology has led us to look into the Some of the earlier results were summarized We confine ourselves here to ob-blood groups in different species. in Dujarric de la Rivigre and Eyquem.' servations that will cover the areas not discussed by the other contributors. Blood Groups in ChimpanzeesThe groups of the same origin previously studied by other workers were composed mainly of animals of group A and a few animals of group 0. No chimpanzee of group B has ever been identified.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 5 publications
1
27
0
1
Order By: Relevance
“…✜ Weakness ✜ Jaundice ✜ Tail tip necrosis ✜ Pigmenturia ✜ Sudden death Feline blood groups worldwide The prevalence of blood groups throughout the world has been studied since Holmes' first report of two distinct blood groups in cats in Manchester, UK. 40 Most studies have been in North America, [49][50][51][52] Europe 43,48,[53][54][55][56][57][58][59][60][61][62][63][64] and Australia, 42,65 with a few studies in South America 66 and Japan. 67,68 Throughout the world type A is the most common blood type, particularly within domestic shorthairs, type B is less common and type AB is considered rare.…”
Section: M P L I C a T I O N S F O R B R E E D E R S 'Fading' Kittementioning
confidence: 99%
“…✜ Weakness ✜ Jaundice ✜ Tail tip necrosis ✜ Pigmenturia ✜ Sudden death Feline blood groups worldwide The prevalence of blood groups throughout the world has been studied since Holmes' first report of two distinct blood groups in cats in Manchester, UK. 40 Most studies have been in North America, [49][50][51][52] Europe 43,48,[53][54][55][56][57][58][59][60][61][62][63][64] and Australia, 42,65 with a few studies in South America 66 and Japan. 67,68 Throughout the world type A is the most common blood type, particularly within domestic shorthairs, type B is less common and type AB is considered rare.…”
Section: M P L I C a T I O N S F O R B R E E D E R S 'Fading' Kittementioning
confidence: 99%
“…Except in primates, no gene mutations have been identified that cause the many animal blood groups. The major blood group system of the domestic cat was identified in the early 1900's [2,3] and was later found to contain two types as determined by agglutination by naturally occurring alloantibodies [4,5]. The two major blood types are called type A and type B [6].…”
Section: Introductionmentioning
confidence: 99%
“…A majority of random bred cats throughout the world are type A [4-6,9-13]. However, some cat breeds have a high frequency of type B individuals.…”
Section: Introductionmentioning
confidence: 99%
“…From those results he proposed a tentative system of nomenclature into groups EF, O, and F 5 . In 1962, the first 2 were designated as types A and B, respectively 6 . In 1980, the third blood type was designated as AB 7…”
Section: Introductionmentioning
confidence: 99%